Analisis Tipologi Perencanaan Kurikulum Pendidikan Pondok Pesantren Sidogiri Pasuruan, Salafiyah Syafi’iyah Sukorejo, dan Al-Amien Prenduan - Ahmad Hosaini (Institut Ilmu Keislaman Annuqayah, 2019)
The research analyzes the typology of the planning of the educational curriculum in three Islamic boarding schools, namely Sidogiri Pasuruan, Salafiyah Syafi'iyah Sukorejo, and Al-Amin Prenduan Sumenep. This field research used a qualitative method and a case study to analyze the characteristics of the planning of the educational curriculum in three Islamic boarding schools mentioned, which were the objects of investigation. This research was conducted between April 2015 and May 2015. The collection data methods were interviews, observations, and documentation study, while the data analysis used was a cross-case analysis of three Islamic boarding schools mentioned.